Onderwys onder die algemene skoolkommissie : die periode 1804-39 - Van der Westhuizen, Wessel Strydom; Park, Margaret; Spoelstra, B.(Bouke),1927- (Stellenbosch : Stellenbosch University, 2012)
Van der Westhuizen's contribution originally approved as thesis for D. Ed. at the University of Stellenbosch.